Perceptions and Attitudes: Analyzing Opinion Leaders in Relation to Genetically Modified Foods - Levy G Randolph II; Joy N Rumble; Hannah S Carter (Journal of Applied Communications, 2018)
Controversial issues in agriculture arise, and it falls on opinion leaders to disseminate information to their networks and the public. Agriculturalists are often blamed for not taken consumers’ concerns into consideration. This study sought to add to previous research by identifying the current perceptions of Florida agricultural leaders toward GM food, what percentage of them identify as opinion leaders with respect to GM food, and what they identify as sources of information regarding GM food. Through an online survey, the trust and attitudes towards GM foods and science, of agricultural leaders who participated in the Wedgworth Leadership Institute, were measured as well as their sources and channels of information. By identifying opinion leaders and helping them understand how to create and disseminate effective agricultural messages, agricultural educators and communicators can reach consumers and reduce the current knowledge gap more successfully. The results of this study confirm previous literature which states that both “what one knows” and “who one knows” impacts the level of influence an opinion leader may have with their peers. Agricultural educators should work with both agricultural opinion leaders and communicators to identify current consumer perceptions and how to address any differences or concerns that arise in interactions.
Keywords: opinion leaders; GM food; perceptions; information sources; attitudes